Extraction, Purification, Structural Characterization and Antioxidant Activity of Polysaccharides from Bracken - Heng LIU; Xiuling ZHANG; Kun LI; Yanqiu BO; Jiaxu LI (Shipin gongye ke-ji, 2023)
In this experiment, dried bracken was used as the raw material, and an ultrasound-assisted method was used to extract and calculate the extraction rate of bracken crude polysaccharides. The bracken polysaccharides were then purified using the Sevage method, macroporous resin, and dialysis method. Chemical composition and physicochemical properties of bracken polysaccharides were determined. Infrared spectroscopy, Congo red test, high performance liquid chromatography, periodic acid oxidation, iodine-potassium iodide reaction, and other methods were used to characterize the structure of bracken polysaccharides, and the antioxidant capacity of bracken polysaccharides on DPPH free radicals, ABTS+ free radical scavenging ability, and FRAP ability were measured in vitro. The extraction rate of bracken crude polysaccharides was 8.91%, the content of purified bracken polysaccharides was 76.95%, the total phenolic content was 1.03%, the content of flavonoids was 1.90%, the sulfate content was 21.38%, and the content of uronic acid was 29.26%, according to the experimental results. The infrared spectroscopy results revealed that bracken polysaccharides had typical polysaccharide absorption peaks, as well as uronic acid and partial pyranose. The monosaccharide composition results revealed that bracken polysaccharide was a heteropolysaccharide made up of ten monosaccharides. Long side chains, more branched chains, complex chain structure, and no three-stranded helix structure of bracken polysaccharide. In vitro antioxidant testing revealed that bracken polysaccharides had a high ABTS+ radical scavenging ability (up to 92.61%), a good iron ion reduction ability (40.15±1.40 mg/g in Trolox equivalent), and a high DPPH free radical scavenging ability. The above findings will serve as a foundation for further research into the structure-activity relationship of bracken polysaccharides, as well as a theoretical reference for the rational use of bracken resources.